Bacterial genomic detection within cerebrospinal fluid of patients with meningococcal disease is influenced by microbial and host characteristics. - Darton, T; Guiver, M; Naylor, S; Kaczmarski, E; Borrow, R; Read, R (2011)
Among 384 patients with confirmed meningococcal disease, the likelihood of detecting Neisseria meningitidis DNA in cerebrospinal fluid (CSF) increased with age, serogroup B infection, and prehospitalization antibiotic treatment. Plasma and CSF genomic bacterial loads of non-B N. meningitidis serogroups correlated significantly. Serogroup B-infected patients with genotype TNF2 (-308A) had significantly higher CSF bacterial loads.